Coming through the Fire : Surviving Race and Place in America - Lincoln, C. Eric (Charles Eric), 1924-2000 (Book collections on Project MUSE., 1996)
Without sidestepping painful issues, or sacrificing a righteous anger, the author argues for "no-fault reconciliation," for mutual recognition of the human endowment we share regardless of race, preparing us as a nation for the true multiculture tomorrow will demand